1995
DOI: 10.1016/s0741-5214(95)70044-7
|View full text |Cite
|
Sign up to set email alerts
|

Flush saphenofemoral ligation and multiple stab phlebectomy preserve a useful greater saphenous vein four years after surgery

Abstract: These findings support the effectiveness of the procedure of flush saphenofemoral ligation and multiple stab phlebectomy with regard to cosmetic and symptomatic outcome and may preserve the GSV for use as an autologous bypass graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…It does confirm previous reports that reflux in the saphenous system does affect usually the thin walled tributaries rather than the LSV itself [7,23]. SFJdisconnection and avulsion of the varicose tributaries confers long-term satisfactory results in more than 85% of patients [22]. Moreover, it has been shown that perforators do not open directly into the LSV they most commonly connect with the tributaries to main vein [22,24].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…It does confirm previous reports that reflux in the saphenous system does affect usually the thin walled tributaries rather than the LSV itself [7,23]. SFJdisconnection and avulsion of the varicose tributaries confers long-term satisfactory results in more than 85% of patients [22]. Moreover, it has been shown that perforators do not open directly into the LSV they most commonly connect with the tributaries to main vein [22,24].…”
supporting
confidence: 86%
“…This issue becomes more important in treating young people with varicose veins. Fligelstone et al [22] performed flush SFJ ligation and avulsion on 72 limbs. They followed these patients for a median of 4 years (3-6 years) after surgery by triplex ultrasound to assess the suitability of the LSV for use as a vascular conduit and to evaluate the objective and subjective cosmetic outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to eliminate saphenous‐derived varicose veins in a durable manner, all sources of reflux into the saphenous axis must be interrupted. While some clinicians believe satisfactory outcomes can be achieved by saphenous‐sparing procedures, which isolate the saphenous vein from reflux, 4–6 we concur with those who feel that better long‐term results may be achieved using an ablative approach 7–9 …”
Section: Discussionmentioning
confidence: 55%
“…Ambulatory phlebectomy has gained more and more interest among phlebologists, first in France where it was introduced in 1966 and worldwide during the past few decades 1 . It is a simple, elegant, definite, and safe treatment modality with excellent cosmetic results for the treatment of varicose veins that has been extensively described in the literature 2–10 . Because of its safety and excellent cosmesis, it has been proposed for the treatment of varicose veins on the legs as well as for other parts of the body such as the arms, the feet, and the peri‐orbital and temporal area 11 .…”
mentioning
confidence: 99%